2017
DOI: 10.1016/j.mad.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction alleviates alpha-synuclein toxicity in aged yeast cells by controlling the opposite roles of Tor1 and Sir2 on autophagy

Abstract: Alpha-synuclein (syn) is the main component of proteinaceous inclusions known as Lewy bodies (LBs), which are implicated in the pathogenesis of the neurodegenerative diseases known as synucleinopathies, like Parkinson's disease (PD). Aging is a major risk factor for PD and thus, interventions that delay aging will have promising effects in PD and other synucleinopathies. Caloric restriction (CR) is the only non-genetic intervention shown to promote lifespan extension in several model organisms. CR has been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
4
13
0
Order By: Relevance
“…The results showed that aSyn toxicity is abolished in rim15Δ cells (Figure g–i), and this phenotype is associated with an efficient arrest in G0/G1 phase and decreased autophagy (Figure j–l). These results are in agreement with those we previously reported showing that the shorter CLS induced by aSyn is abolished by caloric restriction, a physiological intervention that promotes an efficient arrest of cells in G0/G1 through the maintenance of autophagy at homeostatic levels (Guedes, Ludovico, & Sampaio‐Marques, ). Our data establish that the shorter CLS and premature death of cells expressing aSyn are associated with Ras2‐dependent cell cycle re‐entry, S‐phase arrest, and increased autophagy, which are prevented by forcing cells to efficiently arrest in G0/G1 phase.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that aSyn toxicity is abolished in rim15Δ cells (Figure g–i), and this phenotype is associated with an efficient arrest in G0/G1 phase and decreased autophagy (Figure j–l). These results are in agreement with those we previously reported showing that the shorter CLS induced by aSyn is abolished by caloric restriction, a physiological intervention that promotes an efficient arrest of cells in G0/G1 through the maintenance of autophagy at homeostatic levels (Guedes, Ludovico, & Sampaio‐Marques, ). Our data establish that the shorter CLS and premature death of cells expressing aSyn are associated with Ras2‐dependent cell cycle re‐entry, S‐phase arrest, and increased autophagy, which are prevented by forcing cells to efficiently arrest in G0/G1 phase.…”
Section: Resultssupporting
confidence: 93%
“…In addition, inhibition of cell cycle re‐entry of budding yeast cells expressing aSyn by forcing these cells to arrest the cell cycle at G0/G1 phase by RAS2 or RIM15 deletion (Figure ) or caloric restriction (Guedes et al, ), as well as abrogation of DDR by genetic ablation of the MEC1 kinase, protects against aSyn‐mediated toxicity, resulting in an extended CLS. Interestingly, aSyn expression in rat PC12 cells also induces RAS signaling in concert with the accumulation of cells in S‐phase (Lee et al, ), which suggests that growth signaling by RAS‐dependent pathways is a conserved feature of this phenotype of synucleinopathies.…”
Section: Discussionmentioning
confidence: 99%
“…87 In a recent study, Guedes et al explored whether the improved protein quality control associated with CR might rescue the cytotoxicity of α-synuclein expression in aging yeast. 88 They found that α-synuclein toxicity was alleviated by CR, restoring normal chronological longevity. In addition, TOR inhibition (via deletion of TOR1 ) similarly rescued the shortened CLS of α-synuclein–expressing cells.…”
Section: Delayed Chronological Aging In Yeast Models Of Parkinson’s Dmentioning
confidence: 99%
“…CNS neuronal SIRT1 is elevated by both CR (Satoh et al, 2010;Gr€ aff et al, 2013) and physical activity (Falone et al, 2012;Revilla et al, 2014). CR has been shown to be beneficial in PD models (Maswood et al, 2004;Jadiya et al, 2011;Guedes et al, 2016). Physical activities could potentially confer benefit to PD patients in several ways (Speelman et al, 2011), and recent trials have suggested at least a moderate beneficial effect in PD patients (Lima et al, 2013;Uhrbrand et al, 2015).…”
Section: Discussionmentioning
confidence: 99%